2021
DOI: 10.1103/physrevb.103.l060403
|View full text |Cite
|
Sign up to set email alerts
|

Itinerant ferromagnetism mediated by giant spin polarization of the metallic ligand band in the van der Waals magnet Fe5GeTe2

Abstract: We investigate near-Fermi-energy (EF) element-specific electronic and spin states of ferromagnetic van der Waals (vdW) metal Fe5GeTe2. The soft x-ray angle-resolved photoemission spectroscopy (SX-ARPES) measurement provides spectroscopic evidence of localized Fe 3d band. We also find prominent hybridization between the localized Fe 3d band and the delocalized Ge/Te p bands. This picture is strongly supported from direct observation of the remarkable spin polarization of the ligand p bands near EF, using x-ray … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 65 publications
4
10
1
Order By: Relevance
“…The saturation magnetization averaged over in-plane and out-of-plane measurements amounts to Ms = (644 ± 54) kA/m at 10 K, corresponding to a magnetic moment m = (1.95 ± 0.12) µB/Fe. These values are in-line with those previously reported for Fe-deficient Fe5-δGeTe2 (δ = 0.1 -0.3) films exfoliated from bulk crystals 21,33 . Perpendicular to the surface, the saturation field largely increases, indicating an easy-plane magnetic anisotropy.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The saturation magnetization averaged over in-plane and out-of-plane measurements amounts to Ms = (644 ± 54) kA/m at 10 K, corresponding to a magnetic moment m = (1.95 ± 0.12) µB/Fe. These values are in-line with those previously reported for Fe-deficient Fe5-δGeTe2 (δ = 0.1 -0.3) films exfoliated from bulk crystals 21,33 . Perpendicular to the surface, the saturation field largely increases, indicating an easy-plane magnetic anisotropy.…”
Section: Resultssupporting
confidence: 92%
“…We also observed a small polarization of Ge atoms, in agreement with ref. 33 and with our ab initio results (Table 1). As depicted in Figure 4H, both 2p→4d (ΔL=+1) and 2p→4s (ΔL=-1) transitions present a finite XMCD signal.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…In addition, it can be found that the strongly dispersive bands near the Fermi level also come from Fe 3d orbitals, which contribute to the itinerant moments in the magnetic state. Furthermore, the orbital-resolved band structures also reveal that the localized orbitals have distinct hybridizations with some strongly dispersive bands near the Fermi level, which can induce the formation of the Kondo singlets between the local moments and itinerant electrons 58,91 . We consider our results reflect the dual properties of the 3d electrons 58,59,61 , which has been reported for Fe in ironbased superconductors 92 .…”
Section: Discussionmentioning
confidence: 99%
“…[13,14,15,16,17] In general, Fe 5−x GeTe 2 and related Fe 4 GeTe 2 have garnered significant attention recently due to their high ordering temperature and complex behaviors. [18,19,20,21,22,23,24,25,26] The present work was motivated by identifying further routes to tune the magnetism in Fe 5−x GeTe 2 and related bulk phases so that novel properties and logical designs of het-erostructures can be achieved.…”
Section: Introductionmentioning
confidence: 99%